ESTIMASI NILAI KERUGIAN DAN PREMI ASURANSI BANGUNAN AKIBAT BANJIR SUNGAI CITARUM DI KELURAHAN BALEENDAH BANDUNG - Iin Irianingsih; Sukono Sukono; Forman Ivana S. S. S. (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2017)
High rainfall and a lack of soil moisture absorption, often causing over flowing rivers which leads to floods. Flooding due to over flow of Citarum river is a frequent disasters in the district of Bandung which cause losses ranging from loss of property, damage to homes, diseases to loss of life. In this paper discussed about how to estimate loss cost and insurance due to flooding of the Citarum river. In this case alleged that the losses of Citarum floods affected by heads of family suffering, submerged homes, household damages and field damages. Multiple linear regression analysis was used to estimate the loss cost, which used least squares method for estimating model parameters. Mixture of analysis was used to calculate the insurance premium which considered the zone region, social class, loading factor and regulations set by OJK. The results indicate the loss cost is affected by household damage, whileother factors are not significant. Whereas, average premium is 0.5 % of insured amount by calculating the loss cost due to flooding of Citarum river. Based on estimates of loss cost and premium calculation, obtained insurance product in accordance of Baleendah condition.